(untitled) (Bangladesh Journal of Medicine, 2024)
Non-occlusive mesenteric ischemia is a rare but often fatal condition that occurs due to spasms in the splanchnic arteries leading to hypoperfusion, cellular death, bowel ischemia, and eventually perforation. Having a high clinical suspicion in the correct setting is crucial to identifying and treating the medical condition quickly. This is a unique case of an 82-year-old Caucasian male who presented with peritonitis secondary to acute mesenteric ischemia caused by hypotension leading to the eventual finding of bowel ischemia and perforation. Bangladesh J Medicine 2024; 35: 106-109